Knowing When and How to Fight: COVID-19 Between Viral Clearance and Immune Tolerance - Ahmad Utomo (Faculty of Medicine, Diponegoro University, 2020)
ABSTRACTCOVID-19 is a complex disease involving immunological, vascular, and metabolic pathology caused by and consequences of beta-coronavirus SARS-CoV-2 infection. One may use Sun Tzu analogy of war to fight COVID-19 and to survive infection. When enemy has not reached the shore, gathering much intelligence is key to know how the enemy moves and who would be the most vulnerable targets of enemy attacks. Physical distancing, massive nucleic acid testing, and identification of comorbidity may prepare for the incoming enemies. Physical distancing has helped to limit transmission of the virus that mainly due to close contacts with droplets coughed off infected individuals. Moreover, aerosolized virus particles may also contribute to spreading. Nucleic acid testing using real time PCR platform has been a diagnostic gold standard to identify infected individuals during early stage of infection. On the other hand, serological test to capture antibody against SARS-CoV-2 may be useful for immunosurveillance. Discovery of human ACE2 (angiotensin converting enzyme) protein as an obligate partner of SARS-CoV-2 viral entry has provided insights to mechanisms of serious post-infection ramifications to individuals having comorbidities such as hypertension, diabetes or heart conditions. When the enemy reaches ashore, thorough profiling of biomarkers involved in inflammation and coagulation (IL-6, lymphopenia, ground glass opacity, d-dimers, thrombocytopenia) may help predict disease progression and guide treatment strategy. While estimated 80% of infected individuals may recover on their own, the remaining 20% may require hospitalization and serious therapeutic intervention. Several clinical trials are underway such as repurposing existing drugs and evaluating efficacy of convalescence plasma therapy. Finally, vaccine development using genetic engineering may also help control the global spread if it is proven effective.